Survey of Probe Set and Probe Station Selection Algorithms for Fault Detection and Localization in Computer Networks - Patil, Balaji Madhavrao; Pathak, Vinay Kumar (Discoveries in Agriculture and Food Sciences, 2015)
Probing has evolved as a promising approach for fault diagnosis in a network management. It is based on the principle of actively sending out probes in the network to infer the health of network components. Probes are test transactions whose success or failure depends on the health of the probed network components. Probing technique for fault localization involves placement of probe stations (Probe stations are specially instrumented nodes from where probes can be sent to monitor the network) which affects the diagnosis capability of the probes sent by the probe stations. Small probe sets is desirable in order to minimize the costs imposed by probing, such as additional network load and data management requirements. In this paper we have presented an overview of various probe set selection algorithms for network fault detection and localization. We have evaluated these algorithms on a sample network for better understanding.